EXPLORATIVE GEOSPATIAL ANALYSIS OF ROAD TRAFFIC FATALITIES IN NIGERIA FOR THE PERIOD 2005 – 2018 (FUDMA JOURNAL OF SCIENCES, 2022)
Geospatial analysis of road traffic crashes seeks to identify or detect areas of road safety concerns. This paper adopted the number of fatalities per crash to mine for any underlying patterns in road traffic fatality rates in states in Nigeria for the period 2005 â€“ 2018. Four temporal periods were used for the study: 2005-2018, 2005-2009, 2010-2014 and 2015-2018. These data sets were analyzed using the Moranâ€™s I and Getis-Ord statistics. The global Moranâ€™s I results showed that the periods 2005-2018, 2005-2009 and 2015-2018 had a cluster of  fatality rates in Nigeria. Spatial distribution of rates for 2010-2014 were however random. Getis-Ord General G statistics also found cluster in 2005-2018 and 2015-2018 distributions but 2005-2009 and 2010-2014 had random distributions. Anselinâ€™s Moranâ€™s I statistics indicated significant positive spatial autocorrelation for road traffic fatality rates for Kwara and Kogi states (2005-2009), Yobe and Jigawa (2010-2014) and Katsina, Kano, Bauchi and Rivers (2005-2018) while Delta state showed significant negative spatial autocorrelation (2015-2018). Getis-Ord Gi* results detected that the region of significant fatality rates was in the northern states especially of Katsina, Yobe, Jigawa, Kano and Bauchi, which show up more frequently in the study periods. Rivers and Abia states showed up as cold spots. The results generate several opportunities for closer scrutiny of road traffic crash data, for policy and legislation formulation to mitigate road traffic fatalities.
Keywords: Geospatial, Getis-Ord, Moran’s I, road traffic fatality rate, spatial autocorrelation